The impact of industrial agrarian policies on soils: experiences of small-scale farmers in the rural Eastern Cape - Phakisi, Nteboheng Portas (Social Anthropology, 2023)
After the end of legislated apartheid, the South African government changed old policies that had been driven by segregation against the black majority. Black small-scale farmers in rural areas were encouraged to join commercial agriculture to capitalise on state subsidies and support. Municipalities including Buffalo City Metropolitan, Great Kei, Amathole and others in the Eastern Cape, in collaboration with the Eastern Cape Department of Agriculture and agro industry, introduced programmes such as the Massive Food Production Programme and the current Cropping Project to support rural farmers and to reduce poverty in the province. The initiatives included the introduction of genetically modified maize seeds, chemical fertilisers, chemical herbicides, and pesticides, as well as herbicide-resistant and pest-resistant crops. However, joining state-funded initiatives meant farmers had to give up the farming practices and knowledge systems that had sustained them for years, and they lost the kinship they had built with the local soil and its organisms. By kinship I am referring to a symbiotic relationship that does not separate nature from society, a relationship that is mutualistic and in which there is no mastery of one party over the other. Working with rural Eastern Cape small-scale farmers who participated in these programmes, this study employs a multidisciplinary approach to understand the changing agricultural landscape in rural South Africa, focusing on the consequences of state-funded programmes on local soil knowledge in the context of current Eastern Cape industrial agrarian policies. Navigating from small-scale farmers' voices, remote sensing technology, history, African environmentalism, soil science and the human psyche, the study examines what happens when corporations and the government encroach on traditional and small-scale agriculture. This integrative research methodology of the Environmental Humanities, framed from the Global South, compels us to reconceptualise our relationship with nature. The study argues that while agro-industrial technologies can be used with existing local practices to assist farmers, they should never be introduced as a replacement for existing local knowledge of soil fertility. Moreover, where policies focus on the financialisation of the agrarian economy, such policies risk benefitting agrobusinesses instead of poor, small-scale farmers. If policies intended to stimulate rural development are to be effective, the needs of rural small-scale farmers must be taken into consideration when such policies are initiated.